Cutivation of Chlamydia in different cell systems: a comparative study. - Romijn, Phyllis Catharina; Liberal, Maíra Halfen Teixeira (Pesquisa Agropecuaria Brasileira, 2014)
The culture of Chlamydia sp. was tried by three cultivation methods, triturating the lungs and trachea of necropsied animals, and inoculating this suspension in embrionated eggs, mice and cell culture. The technique in which mõnolayers of cell culture were utilized presented the best results, being most practical and swift in diagnosing the disease.